Imre Nagy - Der Held von 1956
Documentary film on Imre Nagy including interviews with János Rainer M., Gábor Görgey, András Hegedűs, György Litván, Mihály Kornis, Miklós Vásárhelyi, Judit Gyenes. Also contains few seconds from the film of the Imre Nagy trial. Katalin Vikol, István Szakály